"Lapps" and "Lapp" objects in northern and western Karelia - Šahnovič, Mark (The Finnish Antiquarian Society, 2021)
This paper deals with the essential and intricate problem of the term Lapps in Russian Karelia. Many researchers from Russia are inclined to think that the term is also applicable to ancient monuments. Thus the term Lapp antiquities would be relevant. The author states that there is no clear archaeological evidence to support this opinion. On the contrary, th e existence of connections between sources of Sámi settlement in Karelia and archaeological sites still remains to be proven in the future.